2013
DOI: 10.1038/mi.2012.111
|View full text |Cite
|
Sign up to set email alerts
|

PD-L2 modulates asthma severity by directly decreasing dendritic cell IL-12 production

Abstract: Studies examining the role of PD-L2/PD-1 in asthma have yielded conflicting results. To clarify its role, we examined PD-L2 expression in biopsies from human asthmatics and lungs of aeroallergen-treated mice. PD-L2 expression in bronchial biopsies correlated with the severity of asthma. In mice, allergen exposure increased PD-L2 expression on pulmonary myeloid dendritic cells, and PD-L2 blockade diminished allergen-induced airway hyperresponsiveness (AHR). In contrast, PD-1 blockade had no impact, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 68 publications
(85 reference statements)
5
42
0
Order By: Relevance
“…PD-L2 is an enigmatic molecule reported to positively and negatively regulate T cells (95101); its effects on B cells are less well-defined. PD-L2 expression is restricted to B-1 cells, memory B cells raised in response to T cell–dependent Ags, macrophages, and dendritic cells (47, 101, 102).…”
Section: Discussionmentioning
confidence: 99%
“…PD-L2 is an enigmatic molecule reported to positively and negatively regulate T cells (95101); its effects on B cells are less well-defined. PD-L2 expression is restricted to B-1 cells, memory B cells raised in response to T cell–dependent Ags, macrophages, and dendritic cells (47, 101, 102).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas both molecules upregulate upon challenge,28 Akbari et al 9 showed that PD-L1 −/− mice had reduced BHR, while PD-L2 −/− mice were protected against ovalbumin-induced experimental asthma. Recently, Lewkovitch et al demonstrated that a high PD-L2 expression on lung mDCs in humans correlated with disease severity8 and peaked in mice around 24 h post challenge while PD-L2 (and not PD-L1) blockade resulted in decreased NSBHR and inhibition of IL-13-induced gene expression. However, as PD-L2 blockade failed to inhibit Th2 cytokine expression, the authors postulated about unidentified ligand(s) to PD-L2 that might have different effects.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their ability to present allergens to naïve T cells, mDCs are able to shape the immune response through the secretion of cytokines and expression of costimulatory molecules. The role of some costimulatory molecules has been recently explored in human asthma,7 including the first and second ligands to programmed death-1 (PD-L1 and PD-L2)8 9 and the ligand to immune costimulator,10 as factors involved in the intrinsic pro-Th2 bias of mDCs from patients with asthma 11 12. mDCs from patients with allergic asthma also have an intrinsic propensity to respond to proallergic epithelial cytokines such as thymic stromal lymphopoietin 13…”
Section: Introductionmentioning
confidence: 99%
“…Finally, most murine allergic asthma models have a strong parenchymal component that is not seen in human disease. Although newer murine models have been developed with the hope of better reflecting SA (or its phenotypes), the relation to human SA has not yet been confirmed (32,33).…”
Section: Animal Models Of Asthma Only Modestly Reflect Human Severe Amentioning
confidence: 97%